A bibliometric and visualized research on global trends of immune checkpoint inhibitors related complications in melanoma, 2011–2021 - Zhang, Hongyi; Shi, Yanlong; Ying, Jianghui; Chen, Yi; Guo, Rong; Zhao, Xin; Jia, Lingling; Xiong, Jiachao; Jiang, Fei (Frontiers in Endocrinology, 2023)
Background Melanoma is a malignant tumor that originates from the canceration of melanocytes with a high rate of invasiveness and lethality. Immune escape has been regarded as an important mechanism for tumor development, while the treatment of immune checkpoint inhibitors (ICIs) is beneficial in restoring and enhancing the body’s anti-tumor immune response to kill tumor cells. To date, ICIs therapy has achieved remarkable efficacy in treating melanoma patients. Despite the significant clinical benefits of ICIs, multiple complications such as rashes, thyroiditis, and colitis occur in melanoma patients. In this study, we aim to explore the development process and trends in the field of ICIs-related complications in melanoma, analyze current hot topics, and predict future research directions. Methods We screened the most relevant literatures on ICIs-related complications in melanoma from 2011 to 2021 in the Web of Science Core Collection (WoSCC). Using VOSviewer, CiteSpace and R language packages, we analyzed the research trends in this field. Results A total of 1,087 articles were screened, and the USA had the highest number of publications (publications = 454, citations = 60,483), followed by Germany (publications = 155, citations = 27,743) and Italy (publications = 139, citations = 27,837). The Memorial Sloan Kettering Cancer Center had the most publications, but the Angeles Clinic and Research Institute had the highest average citation rate. Lancet oncology (IF, 2021 = 54.43) was the most prominent of all journals in terms of average citation rate. Reference and keyword cluster analysis revealed that anti-tumor efficacy, adjuvant treatment, clinical response, clinical outcome, etc. were the hotspots and trends of research in recent years. Conclusions This study offers a comprehensive summary and analysis of global research trends on ICIs-related complications in melanoma. Over the past decade, there has been a significant increase in the number of publications on this topic. However, the safety and benefits of retreatment after the recovery of ICIs-related complications remain unknown. Therefore,the establishment of related prediction models, as well as the immunotherapy of melanoma with ICIs in combination with other adjuvant therapies, are future research hotspots.